Liquidity Management under Fixed Exchange Rate with Open Capital Account - El Hamiani Khatat, Mariam (IMF Working Papers; Working Paper, 2019)
This paper introduces a theoretical framework for liquidity management under fixed exchange rate arrangement, derived from the price-specie flow mechanism of David Hume. The framework highlights that the risk of short-term money market rates un-anchoring from the uncovered interest rate parity due to money and foreign exchange market frictions could jeopardize financial stability and market development. The paper then discusses operational solutions that stabilize money market rates close to the level implied by the Uncovered Interest Rate Parity (UIP). Liquidity management under fixed exchange rate with an open capital account presents specific challenges due to: (1) the larger liquidity shocks induced by foreign reserve swings that challenge the development of money markets; and (2) more complicated liquidity forecasts. The theoretical framework is empirically tested based on the estimate of 'offset' coefficients for Denmark and Hong Kong SAR.